Pengaruh Game Edukasi Monopoly Anemia (GEMA) terhadap Peningkatkan Pengetahuan Tentang Anemia dan Sikap Remaja Putri di Sekolah Menengah Kejuruan Jakarta Selatan - Vira Pratiwi Dias Ayu Putri; Ratna Sari Dinaryanti; Gaung Eka Ramadhan (Universitas Muhammadiyah Manado, 2025)
Anemia is defined as a condition when there is a decrease in hemoglobin and or the number of red blood cells from normal so that there are not enough red blood cells to meet a person's physiological needs. Anemia in adolescents can be influenced by the level of knowledge and attitude towards anemia prevention. This study aims to determine the effect of anemia monopoly educational game (GEMA) on the level of knowledge and preventive attitudes of adolescent girls at SMK South Jakarta. This study used a pre-eksperimental with one-group pretest-posttest design. The population of this study were adolescent girls at SMK South Jakarta with a total sample size of 96 respondents using the Cluster Sampling technique. The research instruments used questionnaires, Monopoly Anemia Educational Game SOP, easy touch tools, and Hb observation sheets. The statistical test used was the Paired T-Test test. The results of the analysis test showed that there was a relationship between the Monopoly Anemia Educational Game (GEMA) and the increase in knowledge of adolescent girls at SMK South Jakarta with a p-value of 0.00 (α<0.05). There is a relationship between Monopoly Anemia Educational Game (GEMA) with an increase in the prevention attitude of adolescent girls in South Jakarta Vocational High School with a p-value of 0.00 (α<0.05). Based on the results of the study, it is hoped that there will be a development of more innovative learning methods regarding education using anemia monopoly.